Genome-wide identification and characterization of the CCT gene family in Chinese cabbage (Brassica rapa) response to abiotic stress - Haoqi Liu; Zhiyuan Yin; Mengping Qiu; Yan Yang; Ye Xu; Han Wang; Min Yan; Guohua Xu (BMC Genomics)
Abstract Background The CCT (CONSTANS, CONSTANS-LIKE and TOC1) gene family plays a crucial role in regulating diurnal rhythms and responding to abiotic stress, which significantly impacts crop growth, development, and yield. However, comprehensive information on the CCT gene family in Chinese cabbage (Brassica rapa) is currently unavailable. Results In this study, we conducted a genome-wide identification and analysis ofCCT genes in Chinese cabbage. In total, we identified 66 CCT genes in the Chinese cabbage genome, and we elucidated the physicochemical properties and subcellular locations of the corresponding CCT proteins. Phylogenetic analysis, examination of conserved motifs, and gene structure analysis revealed that the BraCCT gene family could be classified into three well-conserved subfamilies: COL, PRR, and CMF. The BraCCT gene family has close relationships with Arabidopsis thaliana. Sixty-three pairs of BraCCTs exhibited collinear relationships through interchromosomal synteny analysis in Brassica rapa, indicating that segmental duplication played a vital role in the expansion of the BraCCT gene family. Cis-acting elements of the CCT promoters have been identified to play a role in plant development, hormonal responses, and stress responses. Expression profile analysis showed that CCT genes were extensively expressed in various tissues of Chinese cabbage, exhibiting diverse expression patterns appeared to be diverse. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis of ten CCT genes confirmed their response to heat stress, cold stress, drought stress, and abscisic acid stress. The full-length coding sequence of BraCCT24 was obtained using homologous cloning technology, and further investigation revealed that the BraCCT24 protein is located in the nucleus. Conclusions In this study, 66 CCT genes were identified in Brassica rapa, and their phylogenetic relationships, gene structural features, duplication events, gene expression, and potential roles in Brassica rapa development were investigated. Overall, this study offers a theoretical foundation for further investigating the significant role of the CCT gene family in the functional genome of Chinese cabbage.